2021
DOI: 10.3390/ma14226935
|View full text |Cite
|
Sign up to set email alerts
|

Complex Structural Effects in Deformed High-Manganese Steel

Abstract: The research presented in this paper is part of a larger project concerning deformation behavior, microstructure and mechanical properties of high-manganese steels with different chemical compositions and processed under various conditions. The current investigation deals with the development of microstructure and crystallographic texture of Fe-21.2Mn-2.73Al-2.99Si steel deformed in tension until fracture at ambient temperature. The deformation process of the examined steel turned out to be complex and include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…However, Padilha et al [25], testing AISI 304 austenitic steel after deformation by cold rolling, showed that ε'-martensite formed in steel but at low degrees of deformation up to 5% and then, with an increase in the degree of deformation, it was transformed into α'martensite. ε-martensite as an intermediate phase is also observed in high-manganese austenitic steels [16,17,47]. For the tested steel, there are no diffraction lines from the ε phase in the entire range of deformations of 5-80%, which confirms that the phase transformation in this steel occurs along the γ → α' path.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…However, Padilha et al [25], testing AISI 304 austenitic steel after deformation by cold rolling, showed that ε'-martensite formed in steel but at low degrees of deformation up to 5% and then, with an increase in the degree of deformation, it was transformed into α'martensite. ε-martensite as an intermediate phase is also observed in high-manganese austenitic steels [16,17,47]. For the tested steel, there are no diffraction lines from the ε phase in the entire range of deformations of 5-80%, which confirms that the phase transformation in this steel occurs along the γ → α' path.…”
Section: Resultssupporting
confidence: 60%
“…Annealing of these steels after deformation may lead to the formation of carbides and intermetallic phases [12]. An important structural effect occurring in steels with an austenitic structure Cr-Ni [13][14][15] and high-manganese steels [16][17][18] is the occurrence of a phase transformation during cold plastic deformation, called the TRIP (TRansformation Induced Plasticity) effect and mechanical twinning (called the TWIP effect) [19]. The deformation-induced martensitic transformation is influenced by many factors, such as: temperature, the degree and method of deformation, as well as the chemical composition, size and crystallographic orientation of the austenite grain [20,21].…”
Section: Introductionmentioning
confidence: 99%